P-57 Evaluation of the outcome assessment and complexity collaborative (oacc ) train the trainers workshops. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Russell, Sarah; Dawkins, Marsha; Wolf, Susanne de; Bunnin, Antonia; Reid, Ruth; Murtagh, Felicity
Abstract : Background: The OACC project led by the Cicely Saunders Institute seeks to implement outcome measures to measure, demonstrate and improve palliative care for patients and their families. In collaboration with Hospice UK, four Train the Trainer interactive workshops were delivered March to June 2016. Aims: To enable participants familiar with the OACC measures to train people to implement and use OACC measures in their settings. To evaluate the delivery, relevance and usefulness to practice of the workshops. Method: Evaluation of attendance, workshop delivery, relevance, usefulness to practice and thematic analysis of the free text comments. Results: 98 participants from 46 organisations attended. 87% recommended the workshop to others (1% unsure, 12% did not say). Participants valued practical issues such as further information about OACC, change management, organisational readiness, feeding back data and teaching OACC. Accreditation was of low interest. Thematic analysis of the comments identified the value of networking with others to discuss, reflect experiences, leadership and implementation issues. Conclusion: The evaluation shows the importance of designing workshops to include clinical competences (e.g. knowing and teaching OACC measures) and aspects such as quality (e.g. feedback to improve care), leadership (e.g. change management/organizational readiness) and developing self (e.g. reflection and networking). This is compatible with end of life competency frameworks such as Taylor (2016). Furthermore, the comments indicate the importance of networks of learning to include communities of practice (e.g. space to test ideas), social networks (e.g. opinion and experiences) and teams to share knowledge (e.g. resources) (Jarche 2016). The evaluations emphasised the value of designing workshops to combine clinical expertise with leadership, quality and ongoing networks of learning and resources considerations. This is helpful in the design of future resources and programmes.